The existence of a planet beyond 50 au and the orbital distribution of the classical Edgeworth–Kuiper-Belt objects - Brunini, Adrian (2002)
We study the effects of a Mars-like planetoid with a semimajor axis at about ∼60 AU orbiting embedded in the primordial Edgeworth–Kuiper belt (EKB). The origin of such an object can be explained in the framework of our current understanding of the origin of the outer Solar System, and a scenario for the orbital transport mechanism to its present location is given. The existence of such an object would produce a gap in the EKB distribution with an edge at about 50 AU, which seems to be in agreement with the most recent observations. No object at low eccentricity with semimajor axis beyond 50 AU has been detected so far, even though the present observing capabilities would allow an eventual detection (B. Gladman et al. 1998, Astron. J. 116, 2042–2054; D. Jewitt et al. 1998, Astron. J. 115, 2125–2135; E. I. Chiang and M. E. Brown 1999, Astron. J. 118, 1411–1422; R. L. Allen et al. 2000, Astrophys. J. 549, 241–244; C. A. Trujillo et al. 2001, Astron. J. 122, 457–473; B. Gladman et al. 2001, Astron. J. 122, 1051–1066; C. A. Trujillo and M. E. Brown 2001, Astrophys. J. 554, 95–98). Finally, ranges for the magnitude and proper motion of the proposed object are given.